Catalytic Performance of One-Pot Synthesized Fe-MWW Layered Zeolites (MCM-22, MCM-36, and ITQ-2) in Selective Catalytic Reduction of Nitrogen Oxides with Ammonia - Agnieszka Szymaszek-Wawryca; Urbano Díaz; Bogdan Samojeden; Monika Motak (Molecules, 2022)
The application of layered zeolites of MWW topology in environmental catalysis has attracted growing attention in recent years; however, only a few studies have explored their performance in selective catalytic reduction with ammonia (NH3-SCR). Thus, our work describes, for the first time, the one-pot synthesis of Fe-modified NH3-SCR catalysts supported on MCM-22, MCM-36, and ITQ-2. The calculated chemical composition of the materials was Si/Al of 30 and 5 wt.% of Fe. The reported results indicated a correlation between the arrangement of MWW layers and the form of iron in the zeolitic structure. We have observed that one-pot synthesis resulted in high dispersion of Fe3+ sites, which significantly enhanced low-temperature activity and prevented N2O generation during the reaction. All of the investigated samples exhibited almost 100% NO conversion at 250 °C. The most satisfactory activity was exhibited by Fe-modified MCM-36, since 50% of NO reduction was obtained at 150 °C for this catalyst. This effect can be explained by the abundance of isolated Fe3+ species, which are active in low-temperature NH3-SCR. Additionally, SiO2 pillars present in MCM-36 provided an additional surface for the deposition of the active phase.